User Requirements for Technology to Assist Aging in Place: Qualitative Study of Older People and Their Informal Support Networks - Elers, Phoebe; Hunter, Inga; Whiddett, Dick; Lockhart, Caroline; Guesgen, Hans; Singh, Amardeep (JMIR Publications, 2018)
BackgroundInformal support is essential for enabling many older people to age in place. However, there is limited research examining the information needs of older adults' informal support networks and how these could be met through home monitoring and information and communication technologies. ObjectiveThe purpose of this study was to investigate how technologies that connect older adults to their informal and formal support networks could assist aging in place and enhance older adults' health and well-being. MethodsSemistructured interviews were conducted with 10 older adults and a total of 31 members of their self-identified informal support networks. They were asked questions about their information needs and how technology could support the older adults to age in place. The interviews were transcribed and thematically analyzed. ResultsThe analysis identified three overarching themes: (1) the social enablers theme, which outlined how timing, informal support networks, and safety concerns assist the older adults' uptake of technology, (2) the technology concerns theme, which outlined concerns about cost, usability, information security and privacy, and technology superseding face-to-face contact, and (3) the information desired theme, which outlined what information should be collected and transferred and who should make decisions about this. ConclusionsOlder adults and their informal support networks may be receptive to technology that monitors older adults within the home if it enables aging in place for longer. However, cost, privacy, security, and usability barriers would need to be considered and the system should be individualizable to older adults' changing needs. The user requirements identified from this study and described in this paper have informed the development of a technology that is currently being prototyped.